Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-10T21:05:49+01:00
(5x-3y)(4x-y)=20x²-5xy-12xy+3y²=20x²-17xy+3y²
(3a+2b)(c-b)=3ac-3ab+2bc-2b²
(b-3c)(8b+5c)=-8b²+5bc-24bc-15c²=8b²-19bc-15c²
(5x-4y)(3x-2y)=15x²-10xy-12xy+8y²=15x²-22xy+8y²

licze na naj i mam nadzieje ze pomoglam ;);*
2010-02-10T21:07:53+01:00
(5x-3y)(4x-y)= 20x² - 5xy - 12xy + 3y² = 20x² - 17xy + 3y²
(3a+2b)(c-b)= 3ac - 3ab + 2cb - 2cb = 3ac - 3ab
(b-3c)(8b+5c)= 8b² + 5cb - 24cb - 15c² = 8b² - 19cb - 15c²
(5x-4y)(3x-2y)= 15x² -10xy - 12xy + 8y² = 15x² -22xy + 8y²
2010-02-10T21:08:06+01:00
(5x-3y)(4x-y)=20xkwadrat-5xy-12xy+3ykwadrat=20x kw-17xy+3y kw
(3a+2b)(c-b)=3ac-3ab+2bc-2b kw
(b-3c)(8b+5c)=8b kw+5bc-24bc-15c kw= 8b kw-19bc-15c kw
(5x-4y)(3x-2y)=15x kw-10xy-12xy+8y kw=15x kw-22xy+8y kw